Linguistic adaptation process of peruvian migrants in spanish society - Gonzales Cavero, Rosario Mercedes (2022)
This paper describes and explains the linguistic adaptation of Peruvian migrants who have resided and are currently residing in the Spanish cities of Madrid and Guadalajara; the fact of residing for an extended period of time, more than two years, has influenced in the incorporation of peninsular Spanish expressions to their own idiolect, which leads to the use of their own dialect, Limean, in certain spaces as a referent of their own cultural identity. For the elaboration of this article nine interviews were conducted in order to obtain the testimonies upon which this analysis was based, determining that the Peruvian migrant has gone through the process of convergence, which implied a forced linguistic adaptation, in the social and work environment, due to society's pressure.